Νόμος, φύσις and κόσμος in the Demosthenic Against Aristogeiton 1 - Sørensen, Anders Dahl (Classica et Mediaevalia, 2026)
Ancient literary critics remarked on the peculiarly ‘philosophical’ character of the lawcourt speech known to us as Against Aristogeiton 1, preserved as number 25 in the Demosthenic corpus. In the course of his attack on Aristogeiton, the speaker articulates a remarkable vision of the relation between phusis (nature), nomos (law), and kosmos (order) in the democratic city-state. The aim of the article is to explore the intellectual background to the philosophical ideas contained in the speech and to suggest a set of parallel texts that may help elucidate those ideas. The first part introduces the speech itself and lists the many ways in which it stands out from the rest of the Demosthenic corpus. In addition to peculiarities of style and content, these include aspects of the textual transmission of the speech within the corpus (stichometry). Siding with the majority of scholars who are skeptical about its attribution to Demosthenes, I suggest that we view the speech as a Hellenistic imitation, arguing that rhetorical ‘exercises’ (meletai) from the same period offer a helpful model for thinking about its original cultural and literary context. Proceeding on this assumption, the second part of the article explores the possible sources of inspiration in the ‘philosophical’ sections of the speech. I identify close similarities in thought and formulation in two texts that have not previously been brought into conversation with Against Aristogeiton 1: the Derveni papyrus and the pseudo-Aristotelian De mundo. Much work remains to be done in reconstructing the relation of Against Aristogeiton 1 to these other texts and the traditions they represent. But in identifying some of the intellectual resources on which the author drew in his retrospective portrayal of the trial against Aristogeiton, the article hopes to contribute not only to our understanding of the speech itself, but also more broadly to our understanding of the reception of Classical Athenian democracy in Hellenistic literary culture.